The September 11 terrorist attacks [ - Hillstrom, Kevin , 1963- (Defining moments, 2012)
"Provides a comprehensive account of the origins of Islamic radicalism; the development of Osama bin Laden and al-Qaeda into a deadly force; the horrible events of September 11; the post-9/11 investigations; and the legacy of the 9/11 attacks. Includes a narrative overview, biographies, primary sources, chronology, glossary, bibliography, and index"--Provided by publisher